Take the 2-minute tour ×
Mathematica Stack Exchange is a question and answer site for users of Mathematica. It's 100% free, no registration required.

I want to solve the equation and inequality equation $$\sqrt{8\cdot 16^x - \dfrac{1}{2}\cdot 9^x }= 3\cdot 4^x - 3^x$$ and $$\sqrt{8\cdot 16^x - \dfrac{1}{2}\cdot 9^x } \leqslant 3\cdot 4^x - 3^x.$$ The correct of the given equation is $$-\log_{\dfrac{3}{4}}\left (3+\dfrac{\sqrt{30}}{2}\right ).$$ I tried

Reduce[Sqrt[8 16^x - 1/2 9^x] == 3 4^x - 3^x, x, Reals]
x == Root[{2 + Sqrt[2] 3^-#1 Sqrt[2^(4 (1 + #1)) - 3^(2 #1)] - 
 6 E^(2 Log[2] #1 - Log[3] #1) &, 6.0734320063313606675}]

With inequality, I tried

Reduce[Sqrt[8 16^x - 1/2 9^x] <= 3*4^x - 3^x, x, Reals]
x >= Root[{2 + Sqrt[2] 3^-#1 Sqrt[2^(4 (1 + #1)) - 3^(2 #1)] - 
 6 E^(2 Log[2] #1 - Log[3] #1) &, 6.0734320063313606675}]

How can I get the correct solution?

share|improve this question

3 Answers 3

up vote 6 down vote accepted

This is based on @Nasser solution but improved to make it more general.

If it helps when there are no roots then let's power both sides to 2. But we have to remeber that this will probably lead to double solution. There is a way to get rid of it too:

Equality

expr = Sqrt[8 16^x - 1/2 9^x] == 3 4^x - 3^x;

Solve[ Thread[Power[expr, 2], Equal] && expr, x, Reals]

$\left\{\left\{x\to \frac{\log \left(6+\sqrt{30}\right)-\log (2)}{2 \log (2)-\log (3)}\right\}\right\}$

Inequality

expr = Sqrt[8 16^x - 1/2 9^x] <= 3 4^x - 3^x;

Reduce[Thread[Power[expr, 2], LessEqual] && expr, x, Reals] // Quiet

$x\geq \frac{\log \left(6+\sqrt{30}\right)-\log (2)}{2 \log (2)-\log (3)}$

share|improve this answer

If you first remove the sqrt it seems to help Reduce

\begin{align*} \sqrt{8\left( 16^{x}\right) -\frac{1}{2}9^{x}} & =3\left( 4^{x}\right) -3^{x}\\ \frac{1}{2}\ln\left( 8\left( 16^{x}\right) -\frac{1}{2}9^{x}\right) & =\ln\left( 3\left( 4^{x}\right) -3^{x}\right) \\ \ln\left( 8\left( 16^{x}\right) -\frac{1}{2}9^{x}\right) & =\ln\left( \left[ 3\left( 4^{x}\right) -3^{x}\right] ^{2}\right) \\ 8\left( 16^{x}\right) -\frac{1}{2}9^{x} & =3^{2x}+9\left( 4^{2x}\right) -6\left( 3^{x}4^{x}\right) \end{align*}

ps. To remove the sqrt, much easier to use suggestion by Kuba. No need for taking logs.

Thread[Power[Sqrt[8 16^x - 1/2 9^x] == 3 4^x - 3^x, 2], Equal];
Reduce[%, x, Reals]

Now:

Mathematica graphics

The second solution is what you had

 Simplify[-Log[3/4, (3 + Sqrt[30]/2)] == %[[2, 2]]]
 (* True *)
share|improve this answer
    
@Kuba thanks. Yes, that is easier way to square both sides in order to remove the sqrt root. I just did not know how to do it at the time so took the log of both sides. Will update. thanks. –  Nasser Oct 10 '13 at 9:47
    
No problem. I post my own answer too as I think I can add something new too. :) –  Kuba Oct 10 '13 at 9:50
    
I think, Thread[Power[Sqrt[8 16^x - 1/2 9^x] == 3 4^x - 3^x, 2], Equal]; Reduce[{%, 3 4^x - 3^x >= 0} , x, Reals] // Simplify –  minthao_2011 Oct 10 '13 at 14:16

Since Reduce[Sqrt[8 16^x - 1/2 9^x] == 3 4^x - 3^x, x] gives Reduce::nsmet: This system cannot be solved with the methods available to Reduce you can only resort to some kind of manipulation. You would need to make it more generic and robust, but the closest to what you'do with paper and pencil is :

eq = Sqrt[8 16^x - 1/2 9^x] - (3 4^x - 3^x) ;
eq2 = (eq /. {3^x -> 4^x y, 9^x -> 4^(2 x) y^2}) (* divide by 4^x *)
eq3 = eq2 /. {x -> 0} (* factor out common  terms assuming they are non-zero *)

aux = Reduce[eq3 == 0, y][[2]]
(* 1/3 (6 - Sqrt[30]) *)

Log[3/4, aux] // N (* recall your change of variable *)
share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.